Highlighting Lactic Acid Bacteria in Beverages: Diversity, Fermentation, Challenges, and Future Perspectives - Zahra S. Al-Kharousi (Foods, 2025)
Lactic acid bacteria (LAB) have long been recognized for their versatility and historical significance, with a remarkable capability to produce a wide range of bioactive compounds that can be used across food, pharmaceuticals, nutrition, agriculture, and sustainable industrial sectors. This review aims to explore the current state of knowledge regarding LAB in beverages, emphasizing their diversity across dairy, non-dairy, and hybrid beverage matrices. Key aspects discussed include fermentation processes, associated challenges, and future perspectives. By examining a wide array of studies, this review offers a holistic perspective on the role of LAB in influencing sensory characteristics (both desirable and undesirable), promoting health benefits, extending shelf life, and enhancing their safety. Furthermore, emerging trends are highlighted, such as the use of LAB for the development of novel LAB-based beverages, their use for bioremediation of toxic compounds, genetic engineering of LAB strains to optimize and tailor their fermentation outcomes, and their use in drug delivery.